CRISPR‐Cas9: how research on a bacterial RNA‐guided mechanism opened new perspectives in biotechnology and biomedicine - Emmanuelle Charpentier (EMBO Molecular Medicine)
Graphical Abstract The 2015 Louis‐Jeantet Prize for Medicine winner Emmanuelle Charpentier describes the CRISPR‐Cas9 unique mechanism. The system was harnessed into a new tool that makes genome editing within the cell a simple and straightforward system.